Preventing Recurrence of Crohn's Disease Post-Ileocaecal Surgery in Paediatric Patients: A Therapy Guide Based on Systematic Review of the Evidence - Bronsky, Jiri; Zarubova, Kristyna; Kubat, Michal; Dotlacil, Vojtech (Paediatric drugs, 2024)
BACKGROUND AND AIMS: Ileocaecal resection (ICR) is frequent in paediatric patients with Crohn's disease (pCD). Despite rates of reoperation being low, the risk of clinical or endoscopic post-operative recurrence (POR) is high; effective medical strategies to prevent POR are thus needed. The aim of this systematic review (SR) was to identify and evaluate the published literature on post-operative medical prevention of POR in pCD to draft a possible therapy guide for pCD patients undergoing ICR. METHODS: We performed an SR according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards and registered it in the PROSPERO database (ID: CRD42024533855). The population, intervention, control, outcome (PICO) model was focussed on post-surgical medical prevention of POR in pCD with clearly expressed definition of recurrence (endoscopically using a standardized scoring system (e.g. Rutgeerts score) or by laboratory markers, for example, faecal calprotectin (F-CPT), C-reactive protein (CRP) or by histological findings or by clinical activity indexes [e.g. weighted paediatric Crohn's disease activity index - (w)PCDAI]. From inception until 29 February 2024, the following databases were searched: PubMed/MEDLINE, Scopus/Embase, Web of Sciences, Evidence-Based Medicine Reviews (including Cochrane), Cochrane Central Registrar of controlled Trials (CENTRAL), ClinicalTrials.gov and EudraCT. Retrieved articles were evaluated for eligibility and finally selected publications for risk of bias using ROBINS-I tool. RESULTS: Out of 811 publications identified by the search, only 5 fulfilled inclusion criteria of the SR. None of the studies fully answered our PICO question. The studies were overall of poor quality and the heterogeneity of the data did not allow us to perform meta-analysis, detailed statistical analysis or formal synthesis of data. Adverse events of post-operative medication were not described in any of the included studies. Existing guidelines of European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN), North American Society for Paediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN), European Crohn's and Colitis Organisation (ECCO) and American Gastroenterological Association (AGA) were reviewed and paediatric therapy guide for pCD undergoing ICR was drafted with respect to recent SRs and meta-analyses in adult population and including scarce paediatric data identified by our SR. As pCD patients undergoing ICR are a high-risk population, they should not be left untreated post-operatively. Anti-tumour necrosis factor (anti-TNF) drugs should be considered as first-line therapy in the majority of patients. Non-anti-TNF biologics should be considered in case of anti-TNF failure. Regular endoscopic monitoring starting at 6 months after the surgery and supported by regular F-CPT evaluation should be used to identify early endoscopic recurrence and to escalate the treatment. CONCLUSION: Our SR revealed that there is wide variability in treatment strategies in children, and high-quality data are generally lacking. At the moment, paediatric prophylaxis of POR should be guided by available adult evidence with respect to the high-risk nature of pCD. Extensive research in pCD should be encouraged.
Keywords: Crohn Disease; Child; Recurrence; ileum; dítě; Crohnova nemoc; cékum; sekundární prevence; Postoperative Complications; lidé; pooperační komplikace; Secondary Prevention; Ileum; Humans; Cecum; recidiva